Grace under Pressure Book review - Sansom, Bruce (Dance Books Ltd., Alton,Hampshire (UK), 2004)
Review of Barbara Newman's Grace under Pressure. Like a pearl, a finished performance is beautiful, but hides the vital truth that it started out as a piece of grit. Newman makes it clear that there exist very few artistic directors whose personal desires aren't bombarded by a host of distracting conflicts. PALABRAS CLAVE: artistic directors, Richard Thomas.
Dentro del apartado "Shelf Content".
Grace under Pressure. Barbara Newman, Dance Books, 2004.